The Effect of Electricity Prices on Industrial Electricity Consumption in South Africa - Setshedi, Christinah; Mah, Gisele (International Journal of Energy Economics and Policy, 2025)
Industries face growing pressure to improve productivity and stay globally competitive, making them more vulnerable to fluctuations in electricity prices, as they are energy-intensive. Understanding how electricity price changes affect industrial electricity consumption is crucial for maintaining production efficiency, economic development, and competitiveness. However, limited insights exist in South Africa, especially after the implementation of steep electricity price hikes and the economic impact of Covid-19. The aim of the study was to assess the effect of electricity prices on industrial electricity consumption in South Africa from 1975 to 2023 using the Quantile Autoregressive Distributed Lag (QARDL) model. The results emphasize that high electricity prices negatively affect South African industries, with industrial output similarly having a negative impact on electricity consumption. Conversely, economic growth positively influences industrial electricity consumption. These findings highlight the need for policies that stabilize electricity prices and support industrial electricity consumption while minimizing environmental impacts. The policy implication of rising industrial electricity consumption without reducing output calls for energy efficiency measures, renewable energy adoption, and smart grid development in the industrial sector. Furthermore, policies focusing on stimulating economic growth and demand for goods and services are crucial for boosting industrial production levels.